Human Amniotic Epithelial Stem Cell-Derived Retinal Pigment Epithelium Cells Repair Retinal Degeneration - Li, Jinying; Qiu, Chen; Wei, Yang; Yuan, Weixin; Liu, Jia; Cui, Wenyu; Zhou, Jiayi; Qiu, Cong; Guo, Lihe; Huang, Liquan; Ge, Zhen; Yu, Luyang (Frontiers in Cell and Developmental Biology, 2021)
Age-related macular degeneration (AMD), featured with dysfunction and loss of retinal pigment epithelium (RPE), is lacking efficient therapeutic approaches. According to our previous studies, human amniotic epithelial stem cells (hAESCs) may serve as a potential seed cell source of RPE cells for therapy because they have no ethical concerns, no tumorigenicity, and little immunogenicity. Herein, trichostatin A and nicotinamide can direct hAESCs differentiation into RPE like cells. The differentiated cells display the morphology, marker expression and cellular function of the native RPE cells, and noticeably express little MHC class II antigens and high level of HLA-G. Moreover, visual function and retinal structure of Royal College of Surgeon (RCS) rats, a classical animal model of retinal degeneration, were rescued after subretinal transplantation with the hAESCs-derived RPE like cells. Our study possibly makes some contribution to the resource of functional RPE cells for cell therapy. Subretinal transplantation of hAESCs-RPE could be an optional therapeutic strategy for retinal degeneration diseases.